2011
DOI: 10.1074/jbc.m111.229377
|View full text |Cite
|
Sign up to set email alerts
|

Simple, Automated, High Resolution Mass Spectrometry Method to Determine the Disulfide Bond and Glycosylation Patterns of a Complex Protein

Abstract: Enveloped viruses must fuse the viral and cellular membranes to enter the cell. Understanding how viral fusion proteins mediate entry will provide valuable information for antiviral intervention to combat associated disease. The avian sarcoma and leukosis virus envelope glycoproteins, trimers composed of surface (SU) and transmembrane heterodimers, break the fusion process into several steps. First, interactions between SU and a cell surface receptor at neutral pH trigger an initial conformational change in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…However, these residues could not be studied further since the mutant protein could not fold. In our recently published study (see below) we mapped the disulfide bond pattern of the pre-fusion form of ASLV(A) Env [36]. There are 19 Cys residues in ASLV(A) Env; one residue must be free (Figure 3).…”
Section: Aslv Experimental Systemmentioning
confidence: 99%
“…However, these residues could not be studied further since the mutant protein could not fold. In our recently published study (see below) we mapped the disulfide bond pattern of the pre-fusion form of ASLV(A) Env [36]. There are 19 Cys residues in ASLV(A) Env; one residue must be free (Figure 3).…”
Section: Aslv Experimental Systemmentioning
confidence: 99%
“…However, other glycoproteins may contain one or more occupied glycosylation sites near cysteine residues involved in a disulfide bond. In such cases, a deglycosylation step must be added to the sample preparation to reduce the complexity of the MS/MS data of the disulfide bonded peptides, because glycosylation cannot be simply regarded as a modification on the peptide chains [71, 75, 77]. For example, trypsin digestion of the HIV-1 Env sequence variant, C97ZA012 gp140, which contains 25 N-linked glycosylation sites and 10 disulfide bonds, resulted in seven tryptic, disulfide-linked peptides that all contain at least one occupied glycosylation site on the disulfide-linked chains [75].…”
Section: Sample Preparation For Bottom-up Mass Spectrometric Disulmentioning
confidence: 99%
“…Disulfide bond mapping by profile comparison is usually done using two samples: a protein digest without reduced disulfide bonds (non-reduced sample) and a digest with reduced disulfide bonds (reduced sample). The two samples are separated in two LC runs (experiments), and peptides that are present in the ultraviolet (UV) or total ion chromatogram (TIC) profile of the non-reduced sample, but are absent in that of the reduced sample, are generally considered to be disulfide bonded, and MS/MS data can be used to assign the disulfide bonds [55, 56, 77].…”
Section: Liquid Chromatography-mass Spectrometric Disulfide Bond Amentioning
confidence: 99%
“…Disulfide bonds are another important factor. Mass spectrometry indicated that in Env (ALV-A), a disulfide bond links the two subunits through the first cysteine residue Cys25 in gp85 and the last extracellular cysteine Cys438 in gp37 ( 34 ). Those two cysteines are conserved in all ALV subgroups, including ALV-J.…”
Section: Discussionmentioning
confidence: 99%